2018
DOI: 10.20546/ijcrbp.2018.508.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Length-Weight Relationship of Bombay Duck (Harpadon nehereus) between Juata and Amal

Abstract: The length-weight relationship of Harpadon nehereus was analyzed. Samples were collected from November 2016 to January 2017, in Juata and Amal at Tarakan, North Borneo, Indonesia. The total length measured using a ruler scale 1mm. The total weight measured using a digital platform scales with an accuracy of 1 gr. The lengthweight equation, based on 600 unsexed individuals, was W = 0.006 * L 2.59 at Juata and W = 0.005 * L 3.00 at Amal where W is the total weight (g) and L is the total length (cm). In general t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
1
2
Order By: Relevance
“…However, the finding of the present study revealed that the growth pattern of the male and female fish was characterized by negative allometric (b values of 2.1602 and 2.2665), respectively. This was slightly different from the findings of previous observations of the species in Juata and Amal waters, which showed a b value of 2.59 and 3.00, respectively (Taqwa et al 2018). This implies that there is a possibility that individuals of the Bombay duck in Tarakan waters are getting smaller.…”
Section: Discussioncontrasting
confidence: 93%
“…However, the finding of the present study revealed that the growth pattern of the male and female fish was characterized by negative allometric (b values of 2.1602 and 2.2665), respectively. This was slightly different from the findings of previous observations of the species in Juata and Amal waters, which showed a b value of 2.59 and 3.00, respectively (Taqwa et al 2018). This implies that there is a possibility that individuals of the Bombay duck in Tarakan waters are getting smaller.…”
Section: Discussioncontrasting
confidence: 93%
“…This indicates that the growth pattern of male and female H. nehereus is allometric negative (b<3) which indicates that the gain of weight is slower than the gain of length. There is a slight difference from the findings of the preceding species observations in Juata and Amal waters which obtained b values of 2.59 and 3.00, respectively [4]. This means that there is a chance that individual Bombay ducks in Tarakan waters are getting smaller.…”
Section: Resultscontrasting
confidence: 58%
“…Nomei fish is an economically important fish as it is widely consumed by the locals. However, fresh consumption only accounts for a small amount, most are processed into dry form for national and international markets [3]; [4].…”
Section: Introductionmentioning
confidence: 99%